(untitled) (Al-Qamar, 2023)
Presentation of Islamic concepts, glorious history and the current prospect of the Muslim Ummaah have had been the favorite subject of our Urdu poets. Such content has been presented in various forms and genres but it was specially elaborated in the long poems. Long poem has special features and distinctions. In this article such long poems have been discussed that are compiled in a book and one volume shape. Here are some long poems that have been introduced and discussed in details i.e., wrote long poems with Islamic historical back ground.